THE SILENT PRESSURE: ANALYZING INSTAGRAM’S CONTRIBUTION TO ANXIETY IN COLLEGE STUDENTS - V. Sathishanandan; M. Saravanan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Globally, social media use has been rapidly increasing, particularly among today’s youth. Social media has ingrained itself into everyone’s everyday life. Nonetheless, the largest demographic of social media users is college students, aged 18-21. Instagram is one of the most popular apps among college students. The goal of this study is to draw attention to the relationship between current generation students’ use of Instagram and their anxiety levels. Prior studies have mostly examined how youth mental health is affected by the full range of social media applications. The possibly negative effects of Instagram, the most popular social media app, on anxiety levels, particularly in the 18-21 age range, are not directly addressed by any of the studies. For the younger generation, this could be a cause for concern. College students who use Instagram for three to four hours a day are more likely to experience worry, procrastination, and lack of sleep, according to the hypothesis. A structured questionnaire that was distributed to a random sample of 100 college students helped to validate the hypothesis. The survey obtained responses from 100 participants. Each subject responded to a series of 15 questions. In addition to this survey, the researcher gathered information about psychological and developmental aspects of anxiety from a variety of publications, journals, and magazines.Despite the perception that Instagram fosters more self-expression and community building; there is a definite correlation between increased Instagram usage and a marked decline in motivation and an increase in restlessness. The same is supported by the paper’s findings.